2006 Conference on Lasers and Electro-Optics and 2006 Quantum Electronics and Laser Science Conference 2006
DOI: 10.1109/cleo.2006.4627607
|View full text |Cite
|
Sign up to set email alerts
|

550 mW of blue radiation generated by a frequency doubled mode-locked InGaAs diode laser MOPA system

Abstract: We report on the generation of 550 mW of 460 nm blue radiation by single pass frequency doubling the picosecond pulses of a mode-locked InGaAs diode laser MOPA system in periodically poled KTP.Compact blue laser sources are of interest for many applications such as optical data storage, medical diagnostics, lithography and display technology. Although the operation of blue semiconductor diode lasers has recently been demonstrated [1] the development of reliable high power devices as required for most applicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…By aligning the compressor for shortest pulse duration we found that the pulses emitted by the MOPA system were up-chirped (400 000 fs²). This is in contrast to pulses emitted by actively mode locked laser diodes [5]. The up-chirp is a result of the carrier generation and the dynamic change of the index of refraction in the saturable absorber [6].…”
Section: Jwa118pdfmentioning
confidence: 99%
See 3 more Smart Citations
“…By aligning the compressor for shortest pulse duration we found that the pulses emitted by the MOPA system were up-chirped (400 000 fs²). This is in contrast to pulses emitted by actively mode locked laser diodes [5]. The up-chirp is a result of the carrier generation and the dynamic change of the index of refraction in the saturable absorber [6].…”
Section: Jwa118pdfmentioning
confidence: 99%
“…grating compressor adjustable group delay dispersion to beam diagnostics tapered amplifier optical isolator optical isolator master oscillator with saturable absorber output coupler R=30% Fig. 1: Experimental setup of the diode laser MOPA system with passively mode locked oscillator, tapered amplifier and grating compressor.As shown in previous investigations diode laser based MOPA systems are well suited for the generation of mode locked laser radiation [5]. In contrast to broad-area amplifiers or diode stacks tapered amplifiers (TA) provide radiation in a beam of good spatial quality [5].…”
mentioning
confidence: 98%
See 2 more Smart Citations